Mechanistic model identifies increasing light availability due to sea ice reductions as cause for increasing macroalgae cover in the Arctic - Scherrer, Kim Josefin Niklasdotter; Kortsch, Susanne; Varpe, Øystein; Weyhenmeyer, Gesa Antonie; Gulliksen, Bjørn; Primicerio, Raul (Limnology and Oceanography, 2018)
Source at https://doi.org/10.1002/lno.11043. In the Arctic, rising seawater temperatures and increasing underwater light caused by reductions in sea ice cover are expected to change the structure of arctic marine communities. Substantial, sometimes sudden, increases in macroalgal productivity and biomass have already been observed in arctic rocky bottom communities. These macroalgal responses have been attributed to increasing temperature and light, but the relative importance of the suggested drivers of change has not yet been assessed. In this study, we used a mechanistic competition model to unravel the effects of temperature and light on benthic community structure and algae dominance, focusing on key algae species: red calcareous algae and macroalgal fronds. We find that light is the primary driver of increases in macroalgal coverage, whereas increased seawater temperature plays a secondary role. Shifts leading to macroalgae dominated communities may be mediated by competitive interactions, and are likely due to three light-related processes: earlier sea ice break-out at high latitudes can result in an exponential increase in the cumulative amount of light that enters the water column during a year; threshold effect in light requirements for algal growth; and light requirements of calcareous algae being substantially lower than those of macroalgae. With continued warming, our modeling results suggest that reduced sea ice coverage and increased light availability will favor dominance of macroalgae, which due to their key ecological role are expected to alter the structure and functioning of arctic rocky bottom ecosystems.